PATELLAR REALIGNMENT AND FUNCTIONAL PERFORMANCE IN PATIENTS WITH PATELLOFEMORAL PAIN SYNDROME (International Journal of Physiotherapy, 2016)
Background: Patellar taping is used for pain relief in patients with patello-femoral pain syndrome (PFPS). Yet, there is lack of knowledge regarding its effect on the functional performance. The purpose of the study was to examine the effects of therapeutic patellar taping on the Visual Analogue Scale (VAS) pain scores, number of bilateral squats, and stair climbing time in patients with PFPS.Methods: 30 female patients with PFPS with mean age 20.3± 1.46 years, weight 66.1± 9.68 kg, height 165.83 ± 3.89 cm and BMI 23.91 ± 3.50kg/m2 participated in the study. The subjects were tested randomly under three taping conditions;namely therapeutic, placebo and no-tape. The tested limb was determined to be the affected limb in patients with unilateral affection, and the symptomatic limb in patients with bilateral affection. Data was collected using the Visual Analogue Scale (VAS), Bilateral Squat Test and Timed Stair Ambulation Test.Results: Repeated measures Multivariate Analysis of Variance (MANOVA) revealed that the number of bilateral squats increased significantly (p0.05) in between for the number of bilateral squats and stair climbing time.Conclusion: The findings indicated that therapeutic patellar taping is effective in improving functional performance and reducing pain in patients with patellofemoral pain syndrome (PFPS).